Nonlinear Factors Analysis of Chinese Cross-Cultural Context - Ping, Wu (Sinología hispánica. China Studies Review, 2016)
The context of Chinese international education is a kind of cross-cultural context, and its particularity reflects the structure diversification and multiplicity. This context contains diversity and dynamics in the aspects of the time, place, object, task, psychology, culture and the like. These factors are not arranged and operated in an ordered way, but are endowed with the nonlinear characteristics of uniqueness, openness and polytrope. Language system is often interfered by the internal subtle uncertainty or some minor factors from external interference, can lead to a lot of, unpredictable fluctuations. In Chinese language and Chinese language teaching, there are a lot of nonlinear problems, which cannot be solved by linear analysis. Therefore, the analysis of non-linear factor in Chinese language study is very essential for promoting the development of Chinese language teaching.